Life cycle greenhouse gas emissions of hydrogen imported by maritime transportation: A South Korean case study - Gyuna Kwak; Juha Lee; Yujin Jung; Wonjae Choi (Energy Conversion and Management: X)
Hydrogen has emerged as a key energy source in the pursuit of carbon neutrality. However, resource-deficient countries, including South Korea, find it challenging to produce hydrogen domestically. Therefore, the process of importing hydrogen from overseas is gaining attention as an alternative. This study compares five hydrogen production processes–coal gasification, natural gas steam methane reforming, grid electrolysis, renewable electrolysis, and nuclear electrolysis–and two hydrogen-import processes using liquid hydrogen and ammonia. Reducing emissions from liquefaction and ammonia cracking processes is identified as a critical priority. This study conducts a case study on South Korea while simultaneously analyzing the effects of transport distance and electricity emissions to extend the findings globally. The study demonstrates that the grid electricity emissions in hydrogen-producing countries have a stronger impact than the transportation distance. Consequently, producing hydrogen from regions with cleaner electricity generation is more critical than geographic proximity. Importing ammonia is generally more advantageous than liquid hydrogen, unless the grid electricity emissions are exceptionally low, specifically below 332.1 g-CO2-eq./kWh. Finally, hydrogen requires emissions below 8.55 and 11.89 kg-CO2-eq./kg-H2 to demonstrate an advantage over conventional methods in vehicle operation and power generation, indicating that even hydrogen not meeting clean hydrogen certification standards can outperform traditional approaches. This underscores the need for a more flexible approach to clean hydrogen certification. The comprehensive results of this study are applicable to resource-deficient countries seeking to import hydrogen when they develop as part of their hydrogen-related policies.